2012
DOI: 10.1142/s2010194512008227
|View full text |Cite
|
Sign up to set email alerts
|

Rastall Cosmology

Abstract: We review the difficulties of the generalized Chaplygin gas model to fit observational data, due to the tension between background and perturbative tests. We argue that such issues may be circumvented by means of a self-interacting scalar field representation of the model. However, this proposal seems to be successful only if the self-interacting scalar field has a non-canonical form. The latter can be implemented in Rastall's theory of gravity, which is based on a modification of the usual matter conservation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 19 publications
2
43
0
1
Order By: Relevance
“…Therefore, because λ is constant and the R(4κ λ − 1) = κ T condition applies to all spacetimes and energy-momentum sources, the κ λ = 1 4 case is not allowed [23]. More studies on the various aspects of this theory can be found in [74,[77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: A Brief Review On the Rastall Theorymentioning
confidence: 99%
“…Therefore, because λ is constant and the R(4κ λ − 1) = κ T condition applies to all spacetimes and energy-momentum sources, the κ λ = 1 4 case is not allowed [23]. More studies on the various aspects of this theory can be found in [74,[77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: A Brief Review On the Rastall Theorymentioning
confidence: 99%
“…Observational data from the helium nucleosynthesis seem also in agreement with Rastall gravity [17]. Based on these observational evidences, there have been some recently studies of the various cosmic eras in the framework of Rastall gravity [18][19][20][21][22]. Other interesting a e-mail: cordac.galilei@gmail.com issues are that Rastall gravity seems to do not suffer from the entropy and age problems of standard cosmology [23] and is consistent with the gravitational lensing phenomena [24,25].…”
mentioning
confidence: 90%
“…In this way, Rastall's theory may be viewed as a classical, phenomenological way to implement some concepts that are typical of a quantum theory of gravity. While Rastall's theory has already been studied in the context of the present evolution of the universe [6][7][8][9][10], its application to the primordial universe is still lacking.…”
Section: Introductionmentioning
confidence: 99%